2003
DOI: 10.1002/chin.200340161
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Procedure for the Preparation of 8‐Substituted Guanines.

Abstract: Purine derivatives Purine derivatives R 0540An Improved Procedure for the Preparation of 8-Substituted Guanines. -A variety of novel 8-substituted guanines (V) are synthesized via phosphorus(III)-mediated cyclization of readily available 4-acylamino-5-nitrosopyrimidines (III). -(XU, M.; DE GIACOMO, F.; PATERSON, D. E.; GEORGE, T. G.; VASELLA*, A.; Chem. Commun. (Cambridge) 2003, 12, 1452-1453; Lab. Org. Chem., ETH-Hoenggerberg, CH-8093 Zuerich, Switz.; Eng.) -M. Kowall 40-161

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Synthesis of 8mG : The required 8mG was synthesized from commercially available 6‐chloro‐2,4‐diaminopyrimidine in five steps that are described in detail in the SI. Firstly, 6‐(benzyloxy)‐5‐nitrosopyrimidine‐2,4‐diamine was synthesized in two steps utilizing a methodology developed by Pfleiderer et al42 Secondly, regioselective acylation followed by phosphorus(III)‐mediated cyclisation yielded the benzyl‐protected precursor 6‐(benzyloxy)‐8‐methyl‐9 H ‐purin‐2‐amine, as described by Xu et al43 Unfortunately, the procedure for the benzyl deprotection described by Xu et al provided the formate salt of 8mG, which was not of interest for this study. To obtain the pure 8mG, several deprotection strategies were tested and it was found that palladiumhydroxide (20% on carbon) with cyclohexene as hydrogen donor provided the desired compound 8mG in an acceptable 26% yield.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of 8mG : The required 8mG was synthesized from commercially available 6‐chloro‐2,4‐diaminopyrimidine in five steps that are described in detail in the SI. Firstly, 6‐(benzyloxy)‐5‐nitrosopyrimidine‐2,4‐diamine was synthesized in two steps utilizing a methodology developed by Pfleiderer et al42 Secondly, regioselective acylation followed by phosphorus(III)‐mediated cyclisation yielded the benzyl‐protected precursor 6‐(benzyloxy)‐8‐methyl‐9 H ‐purin‐2‐amine, as described by Xu et al43 Unfortunately, the procedure for the benzyl deprotection described by Xu et al provided the formate salt of 8mG, which was not of interest for this study. To obtain the pure 8mG, several deprotection strategies were tested and it was found that palladiumhydroxide (20% on carbon) with cyclohexene as hydrogen donor provided the desired compound 8mG in an acceptable 26% yield.…”
Section: Methodsmentioning
confidence: 99%
“…17 OH as solvent also led to the formation of the corresponding n-octyl ether, but unlike the above cases, its purification from the solvent molecule, i.e., octyl alcohol, by distillation required an oil bath temperature higher than 125− 130 °C, namely, 145−150 °C. Consequently, the formation of n-octyl 2-(2,4-dioxopteridin-7-yl)benzimidazole-6-carboxylate 8 occurred as a result of hydrolysis.…”
mentioning
confidence: 97%
“…Accordingly, we had to incorporate a methylene group between the guanyl and mannosyl moieties and install the ether bond between the secondary C(3)-OH group of mannose and the C(6)-OH group of an allofuranose. Retrosynthetically ( Scheme 1 ), the ether bond could be formed by ring-opening cyclic sulfate 8 by the alkoxy anion corresponding to alcohol 7 [ 17 ], and the 8-substituted guanine could be formed by regioselective 4 -N- acylation of 2,4-diamino-5-nitrosopyrimidine 9 , followed by reductive cyclization, using a procedure developed by Vasella et al [ 18 ] .…”
Section: Resultsmentioning
confidence: 99%